Proses Pembelajaran Tematik Terpadu dengan Model Problem Based Learning (PBL) di Sekolah Dasar - Widya Krismayanti; Mansurdin Mansurdin (Universitas Negeri Padang, 2022)
This study aims at finding out how Problem Based Learning (PBL) model improves the integreted thematic learning process of the fifth year elementary school students. This study used a classroom action research, conducted in two cycles. This studi used both qualitative and quantitative appoarches. The results of the observations on the Lesson Plan in Cycle I were on an average of 89,28%, categorized in the “good” qualification (G). The results increased to an average of 96,42% in Cycle II categorized in the “very good” qualification (VG). In the learning process during Cycle I, the results of the observations on the teacher and student aspects were on an average of 80,35%, categorized in the “good” qualification (G). The results increased to 96,42% in Cycle II, categorized in the “very good” qualification (VG). In the aspect of students’ knowledge and skills, the results of the observations in Cycle I were on average 75,01% categorized in the “good” qualification (G). The results also increased in Cycle II to an average of 85,14%, categorized in the “very good” qualification (VG). Thus, the results indicate an increase in the integrated thematic learning process using the Problem Based Learning (PBL) model in class V of SD Negeri 20 Indarung, Padang.